2021
DOI: 10.17559/tv-20200108205821
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information Sharing on Different Performance Indicators in a Multi-Level Supply Chain

Abstract: Enterprises can use different methods/principles to obtain competitive advantages. Information sharing (IS) among supply chain (SC) partners is also one of these methods used in enterprises and it has positive effects on overall system performance like reduced inventory level, decreased cost, bullwhip effects and increased profit. In this paper, our aim is to present the impacts of IS on different costs like ordering, holding and penalty costs of each SC member and total system costs in multi SC. We want to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…They concluded that government subsidies can incentivise recycling and remanufacturing, and that remanufacturing costs influence closed-loop supply chain decisions [14,15]. Study the impact of information sharing on multi-tier supply chain indices to generate different levels of performance [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that government subsidies can incentivise recycling and remanufacturing, and that remanufacturing costs influence closed-loop supply chain decisions [14,15]. Study the impact of information sharing on multi-tier supply chain indices to generate different levels of performance [16,17].…”
Section: Introductionmentioning
confidence: 99%